2020
DOI: 10.1002/acm2.13075
|View full text |Cite
|
Sign up to set email alerts
|

Proton vs Hyperarc™ radiosurgery: A planning comparison

Abstract: For many patients, stereotactic radiosurgery (SRS) offers a minimally invasive, curative option when surgical techniques are not possible. To date, the literature supporting the efficacy and safety of SRS treatment techniques uses photon beams. However, with the number of proton therapy facilities exponentially growing and the favorable physical properties of proton beam radiation therapy, there is an opportunity to develop proton therapy techniques for SRS. The goal of this paper is to determine the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Boczkowskiet et al. determined the optimal plan parameters (define the aperture with a tight margin of 0.5mm and use of compensators to better shape distally) on a single metastatic lesion by comparing the proton SRS and photon VMAT SRS treatment plans ( 48 , 49 ). Righetto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Boczkowskiet et al. determined the optimal plan parameters (define the aperture with a tight margin of 0.5mm and use of compensators to better shape distally) on a single metastatic lesion by comparing the proton SRS and photon VMAT SRS treatment plans ( 48 , 49 ). Righetto et al.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, many patients receiving SRS for brain metastasis are being treated to multiple targets at the same time. Although limited literature has shown that proton SRS is technically feasible, 34 their comparison to the photon counterpart did not reflect the modern SRS technolog using photons.…”
Section: Opening Statementmentioning
confidence: 98%
“…Although limited literature has shown that proton SRS is technically feasible, 34 their comparison to the photon counterpart did not reflect the modern SRS technolog using photons.…”
Section: Clinical Benefit Of Proton Srs Is Unclearmentioning
confidence: 98%
See 2 more Smart Citations